HUBUNGAN TINGKAT SPIRITUAL PASIEN DENGAN TINGKAT STRES PADA PASIEN GAGAL GINJAL KRONIS (GGK) YANG MENJALANI HEMODIALISIS - Kurniati, Endah (STIKES Widyagama Husada, 2025)
Chronic Kidney Disease (CKD) is one of the chronic illnesses that significantly affects patients' quality of life. CKD patients undergoing hemodialysis face various physical, emotional, and psychological challenges that can increase their stress levels. This study aims to explore the relationship between patients' spiritual levels and stress levels in CKD patients undergoing hemodialysis. The research method used is descriptive-analytic observational with a cross-sectional approach. The sample consists of 83 respondents selected through purposive sampling. The results show that most respondents have a high level of spirituality (69.9%) and nearly half of the respondents experience moderate stress levels (47%). Spearman's rho analysis indicates a significant relationship between patients' spiritual levels and stress levels in CKD patients undergoing hemodialysis, with a correlation of +0.444, indicating a moderate relationship. This suggests that spirituality plays an important role in stress management, and patients with higher spiritual levels tend to have better coping mechanisms, helping them manage the physical and emotional pressures caused by hemodialysis. Patients with higher levels of spirituality tend to experience lower levels of stress. To help reduce stress in patients, hospitals should strengthen spiritual support through programs such as spiritual counseling, support groups, and training in spiritual relaxation techniques.